EMG EVALUATION OF THE OCCLUSION WITH TEETHAN DEVICE: EFFECT OF THE MUSCLES - Vladimir Bogdanov; Vladimir Petrunov (Peytchinski Publishing, 2024)
Objectives: The aim of the study is to assess the influence of the masticatory muscles on the indices of the occlusion, measured with electromyographic (EMG) device Teethan® (Teethan S.p.A., Milan, Italy). The device is designed to assess the effect of occlusion on muscle balance and thus indirectly guides the clinician to the necessary changes in occlusion. This paper aims to determine whether muscles influence the indices characterizing occlusion. Material and methods: Thirty-three persons aged 13-43 (mean 21.33) years, 15 men and 18 women who fulfilled the criteria, were included in the study. All subjects had a good state of dental and periodontal health and complete permanent dentition. EMG recordings of the masseter and temporalis muscles were performed during maximum voluntary teeth clenching on cotton rolls and in centric occlusion. All values were standardized as a percentage of the maximum clenching on cotton rolls. Results: Most of the results of the test on cotton rolls are below normal reference values provided by the manufacturer. Within the normal range are only the Global index and IMPACT. When compared to MVC in centric occlusion, some of the indices were higher than when biting on cotton rolls (POC MM, BAR, Global index), which pointed out the effect of the occlusal contact on these tests. Conclusions: The calibration of the Teethan® device gives reliable and reproducible results. Test during MVC in centric occlusion will provide information on which of the indices are influenced by occlusal factors. Recording a test MVC on cotton rolls gives valuable information for the muscle balance, excluding the influence of the occlusion.